The Tenth Development Plan (2014–2018) of Turkey and the conceptualization of the regional area. Problems and prospects - Özbek, Oğuz (Dziesiąty Plan Rozwoju (2014–2018) Turcji i konceptualizacja obszaru regionalnego. Problemy i perspektywy, 2015)
This paper discusses in a critical way how the regional area is conceptualized in the Tenth Development Plan of Turkey (2014–2018). The Tenth Plan introduced in 2014 considerably rests on the strategic framework of the preceding Ninth Development Plan (2007–2013). The regional area in Turkey was and is a strategically ambiguous area where the delineation efforts were mostly devoted to the concerns of public administration and territorial sovereignty rather than functional regionalization. The treatment of the regional area in the Tenth Plan seems to confirm this premise. Here, the main topics of the analysis involve new institutional bodies and governance, new and old policy tools of development planning and sustainable development as well as a territorial statistical system. These three analytical areas will be elaborated on by the relevance to geographical representation system, spatial setting and hierarchy. In that vein, the paper attempts to develop a somewhat different view of the development planning in Turkey by focusing on the treatment of the regional area and the spatial context in the latest development plan
Biblioteka Regionalisty, 2015, Nr 15, s. 83-92
Keywords: Turkey; development planning; regional area; Turcja; planowanie rozwoju; obszar regionalny